<span>5x^2-3x-2x^2-(-x^2)-2x^2+3x^3-3x^5*x^-2 = 0
5x^2 - 3x - 2x^2 + x^2 - 2x^2 + 3x^3 - 3x^5 * x^(-2) = 0
5x^2 - 2x^2 + x^2 - 2x^2 - 3x + 3x^3 - 3x^3 = 0
2x^2 - 3x + 3x^3 - 3x^3 = 0
2x^2 - 3x = 0
x * (2x - 3) = 0
x = 0 и 2x - 3 = 0
2x = 3
x = 1,5
Ответ: х = 0 и х = 1,5
</span>
Ответ:
Пошаговое объяснение:
F(y) = x3+9x2-5
F(y)' = 3x2+18x
3x2+18x = 0
3x(x+6) = 0
3x=0 или x+6=0
x=0 x=-6
__.___.____.___._____
-6 -3 0 2
f(-3) = -27 + 81 -5 = 49 - наиб
f(0) = -5 - наим
f(2) = 8+ 36-5 = 39
10,8:2=5,4
5,4-2,4=3
ответ в первом 5,4 очков
во втором 3 очка
Все логично.
60+40=100(км)- расстояние через 1 час
Ответ:на расстоянии 100 км.